2017
DOI: 10.18689/mjv-1000102
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hydatidosis in Camels of Assuit Province, Egypt

Abstract: The present investigation was conducted (during PM examination of the slaughtered carcasses) to assess the prevalence of hydatidosis in camels sacrificed in Assuit Governorate Egypt and to evaluate the sensitivity and specificity of Indirect Enzyme-linked immunosorbent assay (ELISA) in identifying camels infected with hydatid cysts before slaughtering using antigens were precipitated from HCF. Hydatid cyst count and characterization were conducted based on routine meat inspection. Slaughterhouse samples of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Another study reported a seroprevalence rate of 6% in camels harboring hydatid cysts ( 63 ). The frequency of CE observed in camels in the present work is similar to that detected previously by Dyab et al ( 64 ) in Assiut Governorate ( 64 ) and to that reported by Lahmar et al ( 65 ) in Tunisia ( 65 ). In contrast, higher occurrence rates of CE, of 9 and 24.15% were reported in camels from the same region of Egypt ( 66 , 67 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another study reported a seroprevalence rate of 6% in camels harboring hydatid cysts ( 63 ). The frequency of CE observed in camels in the present work is similar to that detected previously by Dyab et al ( 64 ) in Assiut Governorate ( 64 ) and to that reported by Lahmar et al ( 65 ) in Tunisia ( 65 ). In contrast, higher occurrence rates of CE, of 9 and 24.15% were reported in camels from the same region of Egypt ( 66 , 67 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, an in-house Sandwich ELISA procedure was developed using prepared rabbit IgG polyclonal antibodies from the hydatid germinal layers collected during a routine surveillance of CE in the main abattoirs of the Giza governorate. The results of our study showed that lungs and livers are mostly affected with hydatid cysts, as these organs are considered the first large capillary fields encountered by the blood-borne onchospheres [ 42 , 56 ]. This higher incidence of pulmonary echinococcosis than hepatic echinococcosis, reported in our study, might be attributed to the compact tissues of the liver, which may resist developing larger cysts [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five hundred and eighty-seven camels were examined after slaughter from the main abattoirs at Giza and screened for the presence of hydatid cysts and other infections in the camels’ organs. Lungs, livers, and other organs of every animal were examined visually and by palpation for the detection of hydatid cysts [ 42 ]. The infected organs were collected, and the hydatid cysts were separated in phosphate buffered saline (PBS, pH = 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…(2019) Sheep 4300 33 (0.8) Pigs 1235 3 (0.2) Benisuef Zoo donkeys 145 10 (6.9) Liver, lung Aboelhadid et al. (2013) Elminia Cattle/Buffaloes 120/50 6 (5.0)/2 (4.0) Lung, liver Dyab et al (2019) Assiut Camels 200 12 (6.0) Liver, lung, kidney Dyab et al (2017) Sheep 250 (2.4) na Taher & Sayed (2011) Goats 90 6 (6.7) Liver Abdelazeem et al (2020) New valley Sheep 459 37 (8.1) Liver, lung, kidney Osman et al (2014) Goats 528 29 (5.5) Red Sea, Qena, Sohag, Aswan Sheep 820 58 (14.1) Lung, liver, viscera Omar et al. (2013) Goats 130 17 (13.1) Camels 240 12 (5.0) …”
Section: Studies On Cystic Echinococcosis In Egyptmentioning
confidence: 99%